2021
DOI: 10.1039/d1gc03145g
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalysis in ionic liquids: state-of-the-union

Abstract: This perspective reviews the current status and prospects of biocatalysis in ionic liquids. Although they are not strictly speaking ionic liquids, deep eutectic solvents are included because of the close...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 239 publications
0
24
0
Order By: Relevance
“…Moreover, considering the solvent variation can thermodynamically and kinetically affect the process of unfolding and aggregation events, the fine-tuning of cation/anion and hydration solvation by introducing surface substitution might offer intriguing prospects for improving native enzymatic function by preventing the irreversible protein aggregation. Besides the employed halogen-anion (i.e., Cl – ) in the current study, more and more favorable ILs are being applied in the biocatalysis field, ,, such as the IL containing the hydrophobic anion (e.g., bis­(trifluoromethylsulfonyl)­amide ([TFSA] − ) and bis­(fluorosulfonyl)­amide ([FSA] − )). In addition, the studied observables (e.g., structural change, hydration, IL layer) in MD simulation can be easily transferred to other protein–IL systems, which offer the researchers the key to open the protein–IL interaction door.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, considering the solvent variation can thermodynamically and kinetically affect the process of unfolding and aggregation events, the fine-tuning of cation/anion and hydration solvation by introducing surface substitution might offer intriguing prospects for improving native enzymatic function by preventing the irreversible protein aggregation. Besides the employed halogen-anion (i.e., Cl – ) in the current study, more and more favorable ILs are being applied in the biocatalysis field, ,, such as the IL containing the hydrophobic anion (e.g., bis­(trifluoromethylsulfonyl)­amide ([TFSA] − ) and bis­(fluorosulfonyl)­amide ([FSA] − )). In addition, the studied observables (e.g., structural change, hydration, IL layer) in MD simulation can be easily transferred to other protein–IL systems, which offer the researchers the key to open the protein–IL interaction door.…”
Section: Resultsmentioning
confidence: 99%
“…Biocatalysis is an attractive route for synthesizing chemicals and pharmaceuticals in an eco-efficient way. , Biocatalysis in an ionic liquid (IL), , an environmentally friendly and safer alternative solvent, has gained broad interest due to various advantageous properties of ILs (e.g., favorable solubility of substrate/product, homogeneity of the reaction mixture, wider temperature range, easy separation of products). However, the application of hydrophilic ILs in biocatalysis often leads to enzyme deactivation or reduced catalytic activity. …”
Section: Introductionmentioning
confidence: 99%
“…Besides, contrary to popular opinion, the work has also shown higher performance of the lipase derived from a probiotic source than the one obtained from fungal sources. The remarkable activity of the reported biocatalyst can further be enhanced by combining it with strategies like employing ionic liquids, continuous reactor setup, 49,65,66 etc. The present study has thus shown biodiesel production in an eco-friendly and benign-by-design fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Since then numerous examples of the lipasecatalyzed reactions in ILs have been reported. [4,5] Figure 1 shows the progress of publication numbers in the field of ILs in the past 22 years; 125,800 papers in the field of "ionic liquid*" are recorded as an "ionic liquid*". Among them, 3,291 papers and 1,455 papers were recorded as the topics of "enzyme*" and "lipase*", respectively.…”
Section: Introductionmentioning
confidence: 99%